Meningkatkan Minat Baca Kelas 1 SDN Trasan 4 Menggunakan Model Pembelajaran Picture and Picture - Insira, Attalla Cikha (Prosiding University Research Colloquium, 2021)
This study aims to improve students' interest in reading in elementary school grade 1 at SDN Trasan 4 through a learning model. Involving students directly with a total of 10 students consisting of 6 male students and 4 female students. The research method used is Classroom Action Research (CAR) which consists of three cycles where each cycle has stages of planning, action, observation, and reflection. This research consisted of 3 cycles and went through 4 stages, namely, planning, implementation, observation, and reflection. Efforts to increase the reading interest of elementary school students are a shared responsibility, between the students themselves, teachers and parents. The study showed an increase in students' reading ability in grade 1 students at SDN Trasan 4 after the implementation of the Picture and Picture learning model with the average score of students in the first cycle reaching 70.71 with 65.28% completeness and the average score in the second cycle increasing. by reaching 80.00 with a completeness of 89.25%, then in the third cycle it increased with an average value of 95.00 with a completeness of 97.15%. Based on the evaluation results in each lesson, the reading ability of grade 1 students at SDN Trasan 4 has increased with the Picture and Picture learning model.